Faktor Risiko Terjadinya Coronavirus Disease 2019 (Covid-19) pada Penyandang Diabetes Melitus Tipe 2 - Roeroe, Pomantow A. L.; Sedli, Bisuk P.; Umboh, Octavianus (e-CliniC, 2021)
Abstract: Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by SARS-CoV-2 and has been declared as a pandemic by WHO in March 11, 2020. This disease is an additional problem in people with type 2 diabetes mellitus (T2DM). Several studies have shown that diabetes is a risk factor for COVID-19. This study was aimed to determine the risk factors for the occurrence of Coronavirus Disease 2019 (COVID-19) in T2DM patients. This was a literature review study using several journal databases, namely Google Scholar, PubMed, and Science Direct. Literature searching was performed by using the PICOS method and the analysis was carried out qualitatively The results obtained 10 literatures reporting that T2DM would increase the severity and mortality of COVID-19 patients related to elderly age, obesity, chronic systemic inflammation, increased coagulation activity, potential direct damage to the pancreas, changes in expression of ACE2 receptors, dysregulation of the number, activity of immune cells, alveolar dysfunction, and endothelial dysfunction. There was not yet strong evidence regarding discontinuation or continuation of various diabetes drugs in COVID-19 patients, but insulin remains the recommended agent for blood glucose control. In conclusion, T2DM increases the severity and mortality rate of COVID-19 patients Keywords: diabetes mellitus; COVID-19; risk factorsÂ Abstrak: Coronavirus Disease 2019 (COVID-19) merupakan salah satu penyakit infeksi yang disebabkan oleh SARS-CoV-2 dan telah ditetapkan sebagai pandemi oleh WHO pada 11 Maret 2020. Penyakit ini menjadi masalah tambahan bagi penyandang diabetes melitus tipe 2 (DMT2). Beberapa penelitian menunjukkan bahwa diabetes merupakan salah satu faktor risiko terjadinya COVID-19. Penelitian ini bertujuan untuk mengetahui faktor risiko terjadinya COVID-19 pada penyandang DMT2. Jenis penelitian ialah literature review menggunakan laporan penelitian dari beberapa database jurnal, yaitu google scholar, PubMed, dan ClinicalKey. Pencarian artikel menggunakan metode PICOS dan analisis dilakukan secara kualitatif. Hasil penelitian mendapatkan 10 laporan penelitian yang melaporkan bahwa DMT2 meningkatkan tingkat keparahan dan mortalitas pasien COVID-19 akibat adanya mekanisme terkait dengan usia lanjut, obesitas, peradangan sistemik kronis, peningkatan aktivitas koagulasi, potensi kerusakan langsung pankreas, perubahan ekspresi reseptor ACE2, disregulasi jumlah dan aktivitas sel imun, disfungsi alveolar, dan disfungsi endotel. Belum terdapat bukti kuat mengenai penghentian atau pelanjutan berbagai obat diabetes pada pasien COVID-19, tetapi insulin tetap menjadi obat yang disarankan untuk mengontrol glukosa darah. Simpulan penelitian ini ialah DMT2 meningkatkan tingkat keparahan dan mortalitas dari pasien COVID-19.Kata kunci: diabetes melitus tipe 2 (DMT2), COVID-19, faktor risiko